2023
DOI: 10.3390/foods12061343
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Phenolic Acids in The Obtainment of Packaging Materials Based on Polymers—A Review

Abstract: This article provides a summarization of present knowledge on the fabrication and characterization of polymeric food packaging materials that can be an alternative to synthetic ones. The review aimed to explore different studies related to the use of phenolic acids as cross-linkers, as well as bioactive additives, to the polymer-based materials upon their application as packaging. This article further discusses additives such as benzoic acid derivatives (sinapic acid, gallic acid, and ellagic acid) and cinnami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…Ongoing research on DCI's activity will uncover additional therapeutic properties of this safe and natural molecule, while also providing insights into the underlying molecular mechanisms that contribute to its therapeutic potential [37] and also messenger of insulin. [38] Ascorbic acid 2,6-Dihexadecanoate has property of Antimetastatic and anti-invasive and antioxidant action. D-1,2,3,4,5,6-hexanehexol, is a Sorbitol, also called D-Glucitol in the systematic chemical nomenclature, is one type of sugar alcohol (polyols) used in food manufacturing and in medical tests.…”
Section: Quantitative Phytochemical Analysismentioning
confidence: 99%
“…Ongoing research on DCI's activity will uncover additional therapeutic properties of this safe and natural molecule, while also providing insights into the underlying molecular mechanisms that contribute to its therapeutic potential [37] and also messenger of insulin. [38] Ascorbic acid 2,6-Dihexadecanoate has property of Antimetastatic and anti-invasive and antioxidant action. D-1,2,3,4,5,6-hexanehexol, is a Sorbitol, also called D-Glucitol in the systematic chemical nomenclature, is one type of sugar alcohol (polyols) used in food manufacturing and in medical tests.…”
Section: Quantitative Phytochemical Analysismentioning
confidence: 99%
“…Ellagic acid is a naturally occurring phenolic acid that is found in various foods, including fruits, vegetables and some types of fish. Phenolic acids are a type of organic compound that are known for their antioxidant properties and have been associated with a range of health benefits [ 113 ] In the case of ellagic acid, research has suggested that it may have anticancer properties and may be beneficial in the prevention and treatment of various types of cancer [ 114 ]. Ellagic acid is also believed to have anti-inflammatory and antimicrobial effects, which may further contribute to its potential health benefits [ 115 ].…”
Section: Marine Polyphenolsmentioning
confidence: 99%
“…Different proteins, polysaccharides and crosslinking agents exhibit diverse functionalities. Gallic acid (3,4,5‐trihydroxybenzoic acid), is classified as a phenolic acid that includes a carboxylic acid group (COOH) and three hydroxyl (OH) groups which are responsible for its notable antioxidant capacity 2 . Gallic acid has recently been included in the film composition of chitosan, 3 collagen, 4 and gelatin–casein 5 edible films to induce crosslink formation in the film matrix.…”
Section: Introductionmentioning
confidence: 99%